Commentary on “The Feasibility of Hybrid IMRT treatment planning for Left-sided Chest wall irradiation: A Comparative Treatment Planning Study” - Gautam Sarma; Hrishikesh Kashyap; Partha Medhi (Iranian Journal of Medical Physics)
With great interest, we read the article “The Feasibility of Hybrid IMRT treatment planning for Left-sided Chest wall irradiation: A Comparative Treatment Planning Study” by Haldar S et al. (1). We appreciate the interesting observations and their conclusion. However, there are some issues to be further clarified.First, the authors stated that the selected patients had left breast carcinoma with supraclavicular or axillary lymph node involvement. However, they did not specify clearly whether the patients had breast with supraclavicular involvement, breast with axilla involvement, or breast with both supraclavicular and axilla involvement. It would have been better if the authors had provided more detailed information regarding the primary diagnosis of the selected patients. This is important to know as the treatment volume will differ in different groups and whether the results obtained in the study will remain valid for any of the patient groups.Secondly, the volume of the right lung and left lung mentioned in the text are 963.14 ± 175.16 cc and 871.25 ± 171.57 cc, respectively. This contradicts the volumes mentioned in Table 2 for the contralateral lung and ipsilateral lung. This may be a typographical error, and the authors may have inadvertently switched the values for the right and left lung volumes.